Ideology and Polarization Among Women State Legislators. Issue 4 (28th May 2019) - Osborn, Tracy; Kreitzer, Rebecca J.; Schilling, Emily U.; Hayes Clark, Jennifer
Abstract : In early work on women in Congress, scholars consistently identified a tendency among women legislators to be more liberal roll‐call voters than male copartisans. Recent changes in Congress point to the polarization of women, where Democratic women remain more liberal than Democratic men but Republican women are no different from, or more conservative than, Republican men. We use newly available state legislative roll‐call data to determine whether women state legislators are more liberal or polarized than male copartisans. We find that while Democratic women state legislators remain consistently more liberal than male copartisans in most state chambers, Republican women legislators are growing more conservative. Thus, women state legislators are increasingly polarized in most U.S. states. Legislator replacement and increasing polarization among state legislators in office contribute to this effect. We argue that polarization among women legislators has implications for the representation of women in the states.